An Analysis of Gender Representation In English Language Advertisements In Indonesia: A Corpus-Based Study - Nugraha, Cisya Dewantara; Muam, Ahmad; Supriyono, Supriyono (Universitas Negeri Makassar, 2023)
Abstract. The portrayal of gender in advertising has a significant impact on societal gender norms and roles. This study analyses gender portrayals in TikTok advertisements for various products and services. A random sample of 1000 TikTok advertisements for food and beverages, fashion, technology, and finance in the English language was examined. The investigation assessed the gender, functions, and commercial language of characters. The study employed corpus and quantitative analysis. AntConc corpus analysis software was used to capture the data. The research discovered that Indonesian online marketing perpetuates gender stereotypes, specifically by depicting women as passive houseworkers. However, masculine characters were frequently portrayed as aggressive and dominant. The gender representation of products and services varied. Even in English advertisements, the findings shed light on the complexities of gender portrayal in Indonesian internet marketing. Advertisements narrated in English may reflect more egalitarian attitudes on the part of ad creators, but male and female roles continue to imply gender inequality. This highlights the importance of gender equality in online marketing awareness and partnership in Indonesia. To promote diversity and gender equality across all product categories, advertisers and corporations must analyze their promotional language thoroughly. This study also highlights the need for larger sample sizes and additional data in order to completely comprehend gender representation patterns in Indonesian online marketing. The study emphasizes the significance of combating gender stereotypes and promoting gender equality and diversity in global media. Keywords: English, Gender Representation, Online Advertisement, Corpus Analysis, Tiktok